Peroxisome Senescence in Human Fibroblasts - Legakis, Julie E. (The American Society for Cell Biology, 2002)
The molecular mechanisms of peroxisome biogenesis have begun to emerge; in contrast, relatively little is known about how the organelle functions as cells age. In this report, we characterize age-related changes in peroxisomes of human cells. We show that aging compromises peroxisomal targeting signal 1 (PTS1) protein import, affecting in particular the critical antioxidant enzyme catalase. The number and appearance of peroxisomes are altered in these cells, and the organelles accumulate the PTS1-import receptor, Pex5p, on their membranes. Concomitantly, cells produce increasing amounts of the toxic metabolite hydrogen peroxide, and we present evidence that this increased load of reactive oxygen species may further reduce peroxisomal protein import and exacerbate the effects of aging.